Composition and evolution of the North-African lithospheric mantle : petrological and geochemical evidence from mantle xenoliths sampled by cenozoic intraplate volcanism of the Middle Atlas (Morocco) - (:unkn) unknown (My University, 2013)
The Ph.D. study is aimed at characterising the composition of pyroxenite xenoliths brought to the surface by Cenozoic intraplate volcanism in the Azrou Timahdite district of Middle Atlas (Morocco) to unravel their origin and significance in the frame of the geodynamic evolution of the North Africa lithospheric mantle. The interpretations are based on a petrological approach and on reliable geochemical information at both bulk rock and mineral scale. The data are used to address a largely debated and crucial issue, namely whether pyroxenites do represent ancient magmatic events or section of subducted crust recycled into the lithospheric mantle. The geochemical data revealed that the Middle Atlas pyroxenites formed through different processes: 1 – recycling of older oceanic crust in the lithospheric mantle; 2 – reactions between mantle melt and older mafic layers; 3 – magmatic crystallization from enriched melts at mantle depth. In an overall geodynamic scenario, the origin and age of the pyroxenites interpreted as fragments of recycled oceanic crust and as products of melt-Rock interaction processes are not completely understood. By analogy with Ronda and Beni Bousera these pyroxenites could represent old mafic rocks that have been isolated in the subcontinental lithospheric mantle for very long time spans. The fragments of oceanic material and the crustal components recorded by pyroxenites may be tentatively related to subduction processes occurred during Pan-African times. If so, these pyroxenites maintained for long time their pristine geochemical signatures without marked changes.
Keywords: African Research